Impact of polycystic ovary syndrome on the course of the menopausal period - Stachowiak, Grzegorz; Zając, Agnieszka; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Polycystic ovary syndrome is one of the main reasons of hyperandrogenism in women after menopause. Elevated androgen levels generated by polycystic ovaries cause some unfavorable metabolic changes (e.g. in carbohydrate and lipid metabolism), which may lead to increased female morbidity (e.g. diabetes mellitus, metabolic syndrome, arterial hypertension, coronary heart disease, neoplasms – endometrial and ovarian cancers). This has a negative impact on the quality of life of women in this period. Thus, postmenopausal women should be regarded as a group at increased risk of the above diseases and be treated with special medical health care.